Analisis Dan Perancangan Sistem Informasi Akademik Pada STAI An Nadwah Kuala Tungkal - Zaini, Abun; Effiyaldi, Effiyaldi (LPPM Universitas Dinamika Bangsa, 2020)
At STAI A Nadwah Kuala Tungkal has an obstacle in the academic field regarding the final information system of the current task which is conventional so it makes it difficult for students to carry out the process of course contracts, final assignment guidance, reporting and supervision processes.With these obstacles the need for solving by analyzing and designing an academic information system using UML (Unified Modeling Language) system modeling methods include Use Case Diagrams, Activity Diagrams and class Diagrams. This research resulted in a prototype of making an academic information system that has several information services including data majors, student data, lecturer data, submission data proposals, supervisor determination data, examiner determination data, guidance data, submission of exam data which is expected to be an alternative to solving planned to occur at An Nadwah Kuala Tungkal STAI